2012
DOI: 10.1089/apc.2012.0132
|View full text |Cite
|
Sign up to set email alerts
|

Sadness in the SUN: Using Computerized Screening to Analyze Correlates of Depression and Adherence in HIV-Infected Adults in the United States

Abstract: We used a standardized screening tool to examine frequency of depression and its relation to antiretroviral medication adherence among HIV-infected persons on highly active antiretroviral therapy (HAART) in the Study to Understand the Natural History of HIV/AIDS in the Era of Effective Therapy (SUN Study). This is a prospective observational cohort of 700 HIV-infected patients enrolled between March 2004 and June 2006 in four U.S. cities, who completed a confidential audio computer-assisted self-interview [ACA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 60 publications
1
18
0
2
Order By: Relevance
“…[22][23][24] Numerous barriers to HIV medication adherence and overall HIV access to care have been reported, including depression, stigma, disclosure, and drug/alcohol use. [25][26][27][28] A history of trauma or abuse among women with HIV has also been linked significantly to medication nonadherence, 3,11,29 as well as to antiretroviral failure and increased mortality. 2,3,8,11,13 Machtinger and colleagues 3 found that among HIV + biological and transgender women, those who reported recent trauma had over four-times the odds of antiretroviral failure in comparison to HIV + women who did not report recent trauma.…”
mentioning
confidence: 99%
“…[22][23][24] Numerous barriers to HIV medication adherence and overall HIV access to care have been reported, including depression, stigma, disclosure, and drug/alcohol use. [25][26][27][28] A history of trauma or abuse among women with HIV has also been linked significantly to medication nonadherence, 3,11,29 as well as to antiretroviral failure and increased mortality. 2,3,8,11,13 Machtinger and colleagues 3 found that among HIV + biological and transgender women, those who reported recent trauma had over four-times the odds of antiretroviral failure in comparison to HIV + women who did not report recent trauma.…”
mentioning
confidence: 99%
“…18 Moreover, treating mental illness in HIV-infected populations may decrease sexual risk taking, increase prescription of antiretroviral therapy, and improve compliance with HIV treatment. [19][20][21] For these and other reasons, HIV testing is integral to the US National HIV/AIDS Strategy and test-andtreat approaches to HIV prevention. [22][23][24] An evaluation of the 1999 National Health Interview Survey (NHIS) revealed that persons with major depression episodes (including bipolar and schizoaffective disorder), generalized anxiety disorder, and panic attacks were more likely to report ever having had an HIV test than those without these disorders (45.0% vs. 31.1%).…”
mentioning
confidence: 99%
“…Findings by Tedaldi et al (2012) supported this association between depression and nicotine dependence. While the mechanism linking depression with nicotine use is not clear, it is important to note that nicotine dependence is associated with increased rate of depression, pain severity and frequency, and non-adherence to HAART (King et al , 2012).…”
Section: Factors Correlated With Comorbid Depressionmentioning
confidence: 63%
“…other mood disorder. Tedaldi et al (2012) found that depression was significantly more prevalent among women (21.9%) compared to men (11.8%, p=0.005). Likewise, Applebaum, Richardson, Brady, Brief and Keane (2009) found that 77% of women, compared with 44% (P = 0.11; P< 0.05) ofmen were depressed, in a study of67 HIV-positive outpatients.…”
Section: Incidence Of Depression In People Living With Hiv I Aidsmentioning
confidence: 91%
See 1 more Smart Citation